Sobotta Atlas Anatomi Manusia edisi 19 Jilid I : kepala, leher, ekstremitas atas, kulit - [Tidak Terdaftar] (EGC, 1989)
Sobotta Atlas Anatomi Manusia edisi 19 Jilid I : kepala, leher, ekstremitas atas, kulit